Meeting report: risk assessment of tamiflu use under pandemic conditions - Singer, Andrew C.; Howard, Bruce M.; Johnson, Andrew C.; Knowles, Chris J.; Jackman, Simon; Accinelli, Cesare; Caracciolo, Anna Barra; Bernard, Ian; Bird, Stephen; Boucard, Tatiana; Boxall, Alistair; Brian, Jayne V.; et al. (Nat Inst of Environ Health Sciences / The National Institute of Environmental Health Sciences (NIEHS), 2008)
On 3 October 2007, 40 participants with diverse expertise attended the workshop Tamiflu and the Environment: Implications of Use under Pandemic Conditions to assess the potential human health impact and environmental hazards associated with use of Tamiflu during an influenza pandemic. Based on the identification and risk-ranking of knowledge gaps, the consensus was that oseltamivir ethylester-phosphate (OE-P) and oseltamivir carboxylate (OC) were unlikely to pose an ecotoxicologic hazard to freshwater organisms. OC in river water might hasten the generation of OC-resistance in wildfowl, but this possibility seems less likely than the potential disruption that could be posed by OC and other pharmaceuticals to the operation of sewage treatment plants. The work-group members agreed on the following research priorities: a) available data on the ecotoxicology of OE-P and OC should be published; b) risk should be assessed for OC-contaminated river water generating OC-resistant viruses in wildfowl; c) sewage treatment plant functioning due to microbial inhibition by neuraminidase inhibitors and other antimicrobials used during a pandemic should be investigated: and e realistic worst-case exposure scenarios should be developed. Additional modeling would be useful to identify localized areas within river catchments that might be prone to high pharmaceutical concentrations in sewage treatment plant effluent. Ongoing seasonal use of Tamiflu in Japan offers opportunities for researchers to assess how much OC enters and persists in the aquatic environment.
Keywords: antiviral drug ecotoxicology influenza pandemic pharmaceutical pollution sewage treatment plant Tamiflu neuraminidase inhibitors influenza-viruses oseltamivir treatment resistance susceptibility